THE LEADERSHIP OF EDUCATION RESEARCHERS IN LITHUANIAN UNIVERSITIES - Survutaitė, Dalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article gives overview and analyses the changes and development of scientific research on educational sciences in Lithuanian universities in the period of 1990–2004. The prepared and successfully defended dissertations show positioning of the research field of educational sciences: the leadership of education researchers is reflected by the diplomas of habilitated doctors and certificates of pedagogical title of professor. The statistical overview and evaluation of doctoral dissertations in the research field of educational sciences (social sciences) in the period of 1990–2004 reveal that training of education researchers occurred both in separate universities and in the networks of universities. The distribution of researchers in Lithuanian higher education is also discussed. The statistical data on habilitated doctors in social sciences and doctoral dissertations in education defended in the period of 1990–2004 illustrate the need to develop researchers of highest qualification in Lithuanian universities. The case study of Lithuanian University of Educational Sciences allows revealing the leadership of education researchers in training of doctoral students.